Spectroscopic and Magnetic Study of Mixed Ligand Complexes with Divalent Transition Metals Using Azo-Azomethine Ligands - Alwan, Ali Hussein Mohammed (University of Thi-Qar Journal, 2025)
The research involves the synthesis and characterization of a number of mixed ligand complexes with divalent cobalt, nickel, copper, and zinc ions, using a new homocyclic azo-azomethine ligand 1-(4-(1-(p-tolylamino) ethyl) phenyl) diazanyl) naphthalen-2-ol (TEPDN) and two organic ligands: HL2 (o-aminophenol) and HL3 (anthranilic acid). The results indicated that the mixed ligand complexes have a molar ratio of (metal:ligand) (1:1:1). The spatial structures of the mixed ligand complexes were proposed based on the results of UV-Vis spectroscopy, in addition to magnetic susceptibility and molar conductivity measurements of the synthesized chelated complexes. Tetrahedral geometries were suggested for the cobalt (II) and zinc (II) complexes, while square planar geometries were proposed for the nickel (II) and copper (II) complexes